PERSYARATAN KANDUNGAN LOKAL (LOCAL CONTENT REQUIREMENTS) DI INDONESIA DAN KAITANNYA DENGAN PERJANJIAN INTERNASIONAL DI BIDANG INVESTASI - Esty Hayu Dewanti (Universitas Airlangga, 2012)
As a popular policy in developing countries, local content requirement requires the multinational corporation to use certain amount of components which are produced in the host country in order to give protection to the local industries (national protection). The local content policy has given benefits for developing countries such as an expansion of employment and transfer of technology to the society. Due to the reasons, Indonesia also implemented the local content policy in various sector for example automotive, electronic, oil and gas, etc and it has been legalize in the Indonesian technical regulation. On the other hand, the local content policy violated the national treatment principle which is stated in Article III, 4 GATT and paragraph 1A Annex TRIMs. The national treatment principle defined as the principle which gives the foreign investors/investment no less favorable treatment than the local investors/investment. It is realized that the local content policy has raised the discrimination of some imported product and it should be abolished within certain period as stated in TRIMs.Keywords: local content requirements, national treatment, national protection